Women’s Consultant Participation In The Malaysian Construction Industry - Jaafar, Mastura; Nuruddin, Azlan Raofuddin; Mazlan, Norliza (Construction Research Institute of Malaysia (CREAM) MAKMAL KERJA RAYA MALAYSIA, 2015)
It has been over a decade that the number of women entering construction related programmes in Malaysian higher education has outnumbered men. However their numbers of involvement in the industry is very much lower compared to men and has not been extensively documented. The aim of this paper is to establish the level of women’s participation in the construction industry and to identify the barriers and challenges faced by women in this sector. A questionnaire survey has been administered to 45 women working in consultancy irms in the construction industry through simple random sampling. Majority of the respondents were in the category of having 1-10 years of industry experience. Their decision to enter the industry has been inluenced either by parents, themselves or friends and motivated by inancial gains and good career opportunities. The main barrier to remain in the construction industry is the inlexible working hours and the most challenging factors faced are mistreatment by others in the industry and strict recruitment processes. The indings bring an important message to the consultant organizations, to continue their support on this cohort, especially those with family obligations, by developing lexible work schedules and looking at cases of mistreatment seriously. In anticipation of the industry recruiting higher number of women workers in the future, it is thus timely that the industry should formally acknowledge their existence and contribution. Adopting lexible working arrangements would greatly facilitate in the development and enhancement of this potentially important asset to sustain in the industry.